Types of Intertextuality - Gjurgjan, Ljiljana Ina (Array, 2008)
The essay starts with the contention that there is a fundamental difference between allusion and intertextuality since allusion refers to authorial reference to some other text(s) whereas intertextuality addresses the ways in which a text is interwoven within cultural signifying practices. Moreover, though the study of allusions informs the reading, it is not as important to the process of sense making or to the ethicity of reading as is the intertextual dynamics between a text and its intertext. The argument proceeds by differentiating among three types of intertextuality: subversive, adaptive and transpositional, the first being characteristic of modernism and the second of postmodernism. Transpositional intertextuality is particularly significant for postcolonial studies since it addresses the problem of cultural dynamics between the centre (metropolis) and periphery, which redefines not only periphery but the center as well.